2013
DOI: 10.1002/jgre.20123
|View full text |Cite
|
Sign up to set email alerts
|

Antipodal terrains created by the Rheasilvia basin forming impact on asteroid 4 Vesta

Abstract: The Rheasilvia impact on asteroid 4 Vesta may have been sufficiently large to create disrupted terrains at the impact antipode. This paper investigates the amount of deformation expected at the Rheasilvia antipode using numerical models of sufficient resolution to directly observe terrain modification and material displacements following the arrival of impact stresses. We find that the magnitude and mode of deformation expected at the impact antipode is strongly dependent on both the sound speed and porosity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…In this second location, the topography is partly the result of the fresh crater Torquata and of a ridge of unit Sfc. The crater Torquata is also located close to the Veneneia antipode (65°N/350°E), where antipodal uplift could be expected (e.g., Bowling et al, 2013;Blewett et al, submitted for publication). The ejecta of the Varronilla basin would need to be unevenly distributed to create an elevated area only near 47°N/62°E and near Torquata.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this second location, the topography is partly the result of the fresh crater Torquata and of a ridge of unit Sfc. The crater Torquata is also located close to the Veneneia antipode (65°N/350°E), where antipodal uplift could be expected (e.g., Bowling et al, 2013;Blewett et al, submitted for publication). The ejecta of the Varronilla basin would need to be unevenly distributed to create an elevated area only near 47°N/62°E and near Torquata.…”
Section: Discussionmentioning
confidence: 99%
“…The NE-SW ridge that truncates the Postumia basin could have formed by a large-scale fault. North of the fault, part of the Postumia basin may have been lifted up by antipodal effects of the Veneneia or Rheasilvia impacts (e.g., Blewett et al, submitted for publication; Bowling et al, 2013). In-depth analyses and a discussion of the tectonic features that characterize unit Sft are presented by Scully et al (2014).…”
Section: Geologic Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dawn compositional data were compared with the large body of petrologic, geochemical, and geochronologic studies of HED meteorites (e.g., Keil, 2002;McSween et al, 2011, and references therein), which have been demonstrated to have come from Vesta or its associated vestoid family (McSween et al, 2013a). Mathematical computer modeling of large impact events (e.g., Jutzi and Asphaug, 2011;Bowling et al, 2013) has also aided in interpretation of Dawn data.…”
Section: Methodsmentioning
confidence: 99%
“…Our goal was to identify key geologic events recorded on the surface of Vesta, as recognized through mapping and other studies (e.g., Buczkowski et al, 2012;Bowling et al, 2013), and from them synthesize a timestratigraphic scheme and geologic time scale.…”
Section: Methodsmentioning
confidence: 99%